Gandhi: A Man for our Times? - Judith Brown (Journal for the Study of Religion)
Following my earlier collaboration with Martin Prozesky, my essay links with three major concerns in Prozesky’s work as he has engaged with a radical critique of religious traditions and structures in the South African context of the end of apartheid: the involvement of dominant religious traditions in sustaining power structures and inequality; the nexus between religious beliefs and organizations and violence; and the failure of many ‘religions’ to meet the needs of serious seekers after meaning and truth. In this context, I examine the life and thought of M.K. Gandhi, particularly the way he addressed the nature of India and its problems as British imperial rule ended. It also focuses on Gandhi’s critique of Hindu tradition as a powerful buttress of profound social inequality particularly relating to caste and gender; his response to violence in the name of religion and community; and finally his underlying belief that true religion was the individual’s search for the divine and that all religious traditions by contrast have very partial visions of truth. Finally, in my view, Gandhi should be seen not just as an important historical figure but very much as a man for our times also.